Group Counseling Self-Control Technique Based on Surat Al-Imran Verse 134 to Overcome Aggressive Behavior in Students: Is it Effective? - Nida Arrohmah; Abi Fa’izzarahman Prabawa (Pamomong: Journal of Islamic Educational Counseling, 2023)
The occurrence of violence and aggressive behavior in schools needs special attention and treatment. This study aimed to determine the effectiveness of behavioral group counseling self-control techniques based on Surah Al-Imran verse 134 to overcome aggressive behavior in students. The type of research is a quantitative pre-experiment using the One-Group Pretest-Posttest Design. Respondents in this study amounted to 12 students who were taken using a purposive sampling technique. The instrument used in this study was an adaptation of the aggressive scale from Buss & Perry (1992). The instrument consists of 30 items with a validity value of > 0.3 and a reliability of .912. The results of the paired t-test showed p=.002; p < 0.05. That is, group counseling of self-control techniques based on Surah Al-Imran Verse 134 is effective for overcoming students' aggressive behavior.